Egypt Health Policy Note : Egypt Public Expenditure Review - World Bank (Washington, DC, 2012)
The public expenditures review (PER) of the health sector was prepared in response to a request from the government of Egypt as part of a broader PER work that covers other sectors. This policy note is intended to inform government policymakers of the key findings from the PER and recommend strategies for improving the efficiency, equity, and sustainability of public financing in the health sector, with a special emphasis on expanding the coverage of social health insurance - a major plank in the health reform strategy announced by President Mubarak in July 2005. There are four sections in the report. The first section provides background information. The second section presents a summary of health outcomes, trends, and financing in Egypt; an analysis of inequities in the allocation and utilization of health resources; and an assessment of the efficiency of the delivery of health services. The third section summarizes existing government policies toward the health sector. The fourth section proposes strategies and recommendations for expanding social insurance coverage and enhancing incentives to deliver health services more efficiently and effectively.